The impact of employee engagement on intention to leave in SMEs in Lebanon: the moderating role of normative commitment - Alfred M. Osta (Cogent Business & Management)
High rates of employee turnover continue to be a global issue for companies. The intention to leave an organization, the leading predictor of actual employee turnover, is triggered by several factors which are not thoroughly studied in the extant literature. In response, data was collected from 56 Lebanese SMEs through the distribution of questionnaires and analysed under the quantitative and empirical research model. The purpose of the study is to explore the interplay between employee engagement, normative commitment, and the intention to leave through the prevalent lens of job demands-resources. The findings reveal original empirical evidence confirming a moderating role of normative commitment on the proposed relationship; and, ultimately, the decision to quit is negated. The paper contributes a heightened comprehension of the interplay between employee engagement and normative commitment in Lebanese SMEs; particularly after the pandemic. The author explains the implications and limitations, highlighting the need to reevaluate the conclusions in relation to the ‘new normal’ brought by Covid-19. These results can help organizations and managers who are keen to reduce employee turnover. To conclude, the study established calls for potentially fruitful research studies.